Analisis Strategi Bumdesa Wijaya Dalam Upaya Pengembangan Bisnis Di Desa Warurejo - Devi Indra Putri Prasetya; Mohammad Rizal; Tri Sugiarti Ramadhan (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract The title of this study is “Wijawa BUMDesa Strategy Analysis in Business Development Efforts in Warurejo Village ". The aim of the research is to find out the business competitive strategy in order to maintain business existence in the face of the rise of companies around BUMDESA Wijaya. Primary data collection was carried out through in-depth interviews with the information in this study. Secondary data was obtained through literature studies, research journals, an overview of BUMDes "WIJAYA" Warurejo Village. The research method used is a qualitative descriptive analysis method. The analytical method used is SWOT analysis, IFE matrix, EFE matrix, and SWOT matrix. The results of the IFE and EFE matrices show that the BUMDesa quadrant position is in Quadrant I. This position shows that the profitability is very high BUMDesa has opportunities and strengths to take advantage of existing association opportunities. The recommended strategy is that human resources must be applied even better. Based on the SWOT analysis and the development of strategies that can be implemented to support the welfare of the people of Warurejo Village. Keyword: Strategic BUMDESA Wijaya, Business Development Efforts